HYBRID WORDS IN THE UZBEK LANGUAGE: LINGUISTIC AND SEMANTIC ASPECTS - Turdaliyeva Shahnoza Uktamovna (Western European Studies, 2025)
The Uzbek language, shaped by centuries of interaction with other linguistic communities, contains numerous hybrid words formed through contact with Arabic, Persian, Russian, and English. This study explores the formation, classification, and semantic adaptation of hybrid words in Uzbek. The research examines how borrowed elements integrate into Uzbek phonetics, morphology, and syntax, resulting in hybrid lexical units. Additionally, the study highlights the cultural and historical significance of hybridization in Uzbek and compares it to similar processes in English.
Keywords: Hybrid words; Uzbek language; linguistic borrowing